2013
DOI: 10.1784/insi.2012.55.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Resolution enhancement of ultrasonic B-mode images

Abstract: IntroductionThe signal received from an ultrasound transducer contains information about the component on which the transducer is placed. When the amplitude of this signal is plotted on a colour scale against transducer position, a cross-section representation of the component is created; these are called B-scan images. B-scan images are an extremely useful tool to the NDT technician, allowing them to 'see' inside a component. B-scan images can be created by measuring the distance a single transducer has moved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While obtaining the crack propagation path and orientation by adopting TFM, Camacho et al showed that sizing by tip detection with phase coherence imaging (PCI) was more robust than the 6 dB drop approach [12]. In addition, signal and image processing techniques were developed which improve the time resolution of the measured A-scan signals [13], [14] and spatial resolution of the ultrasonic images [15], [16]. However, when the defect size is comparable to the ultrasonic wavelength, the defect indication becomes indistinguishable from that of a point scatterer and image-based characterisation of small defects is fundamentally challenging.…”
Section: Introductionmentioning
confidence: 99%
“…While obtaining the crack propagation path and orientation by adopting TFM, Camacho et al showed that sizing by tip detection with phase coherence imaging (PCI) was more robust than the 6 dB drop approach [12]. In addition, signal and image processing techniques were developed which improve the time resolution of the measured A-scan signals [13], [14] and spatial resolution of the ultrasonic images [15], [16]. However, when the defect size is comparable to the ultrasonic wavelength, the defect indication becomes indistinguishable from that of a point scatterer and image-based characterisation of small defects is fundamentally challenging.…”
Section: Introductionmentioning
confidence: 99%